The impact of anthracyclines in intermediate and high-risk HER2-negative early breast cancer-a pooled analysis of the randomised clinical trials PlanB and SUCCESS C - De Gregorio, Amelie; Janni, Wolfgang; Friedl, Thomas W. P.; Nitz, Ulrike; Rack, Brigitte; Schneeweiss, Andreas; Kates, Ronald; Fehm, Tanja; Kreipe, Hans; Christgen, Matthias; Kuemmel, Sherko; Trapp, Elisabeth; et al. (British Journal of Cancer, 2022)
Background Anthracycline/cyclophosphamide-taxane-containing chemotherapy (AC-T) is the standard of care in the adjuvant treatment of HER2-negative early breast cancer (EBC), but recent studies suggest omission of anthracyclines for reduced toxicity without compromising efficacy. Methods Based on individual patient data (n = 5924) pooled from the randomised Phase III trials PlanB and SUCCESS C, we compared disease-free survival (DFS) and overall survival (OS) between intermediate to high-risk HER2-negative EBC-patients treated with either six cycles of docetaxel/cyclophosphamide (TC6) or an AC-T regime using univariable and adjusted multivariable Cox regression models. Results AC-T conferred no significant DFS or OS advantage in univariable (DFS: hazard ratio (HR) for TC vs. AT 1.05, 95% confidence interval (CI): 0.89-1.24, P = 0.57; OS: HR 1.00, 95% CI: 0.80-1.26, P = 1.00) and adjusted multivariable analysis (DFS: HR 1.01, 95% CI: 0.86-1.19, P = 0.91; OS: HR 0.97, 95% CI: 0.77-1.22, P = 0.79). Patients receiving TC6 had significantly fewer grade 3-4 adverse events. Exploratory subgroup analysis showed that AC-T was associated with significantly better DFS and OS in pN2/3 patients, specifically in those with lobular histology. Conclusion For most patients with HER2-negative EBC, AC-T is not associated with a survival benefit compared to TC6. However, patients with lobular pN2/pN3 tumours seem to benefit from anthracycline-containing chemotherapy.
CRIS-Team WoS Importer:2022-03-18